Health literacy and independently associated factors in older adults : A systematic review - Kallioinen, Liisa (My University, 2022)
Health literacy is a capacity to obtain, comprehend, and use health-related information to make judgments and decisions concerning well-being and health. Inadequate health literacy is an essential factor that decreases a person’s possibilities to operate in the health care environment. Older adults have health-related problems and need health care services more often. The aim of this study was to investigate the level of health literacy in older adults and factors independently associated with health literacy. A systematic review was conducted in two databases, PubMed and CINAHL, resulting 80 articles that met the inclusion criteria. The quality appraisal of the articles was made by using STROBE or CONSORT checklists. The analysis of the articles was conducted by content analysis. Categories and subcategories were identified and analysed. The methodologies, study populations, and outcomes of the reviewed articles were heterogeneous. However, the results showed that generally at least one third of older adults have limited level of health literacy. The study identified sociodemographic factors and other outcomes that are associated with health literacy. Sociodemographic factors associated with health literacy are age, education, financial status, employment, and minority status. Gender does not have clear independent association with health literacy. Other outcome categories identified in this study, that are at least in most of the articles independently associated with health literacy, are health, functionality, health promotion and health care utilization. Health illiterate older adults tend to have poorer health and functionality, practice less health promoting behaviors and need to use health care services more. The conclusion is that there is an alarming group of vulnerable older adults, who are in danger of not getting the care and guidance that they need in health care. It is important to provide solutions and to take actions to improve the level of health literacy in older adults and reduce the disparities between health literate and illiterate older adults.

Terveydenlukutaito on yksilön kyky hankkia, ymmärtää ja käyttää terveyteen liittyvää tietoa tehdäkseen arvioita ja päätöksiä koskien terveyttä ja hyvinvointia. Puutteellinen terveydenlukutaito on keskeinen tekijä, joka vähentää ihmisen mahdollisuuksia toimia terveydenhuollon ympäristössä. Ikääntyneillä on enemmän terveyteen liittyviä ongelmia ja tarvitsevat terveydenhuoltoa. Tämän tutkimuksen tarkoitus oli tutkia ikääntyneiden terveydenlukutaidon tasoa ja tekijöitä, jotka ovat siihen itsenäisesti yhteydessä. Systemaattinen kirjallisuuskatsaus tehtiin kahdessa tietokannassa, PubMedissa ja CINAHL:ssa, jonka tuloksena saatiin 80 sisäänottokriteerit täyttävää artikkelia. Artikkeleiden laaduntarkistus tehtiin käyttämällä STROBE- tai CONSORT-tarkistuslistaa. Aineiston analyysi tehtiin sisällönanalyysillä. Kategorioita ja alakategorioita tunnistettiin ja analysoitiin. Katsauksen artikkeleiden metodologiat, populaatiot ja tulokset olivat heterogeenisiä. Tulokset osoittivat kuitenkin, että yleisesti ainakin kolmasosalla ikääntyneistä on puutteellinen terveydenlukutaito. Tutkimuksessa löydettiin sekä sosiodemografisia että muita muuttujia, jotka ovat yhteydessä terveydenlukutaitoon. Sosiodemografisia tekijöitä ovat ikä, koulutus, tulotaso, työllisyys ja vähemmistöasema. Sukupuolella ei ole itsenäistä yhteyttä terveydenlukutaitoon. Muita terveydenlukutaitoon yhteydessä olevien tekijöiden kategorioita ovat terveys, toiminnallisuus, terveyden edistäminen ja terveydenhuollon käyttäminen. Ikääntyneillä, joilla on matala terveydenlukutaito, on huonompi terveys ja toiminnallisuus, ja he harjoittavat vähemmän terveyttä edistäviä käytäntöjä ja tarvitsevat enemmän terveydenhuollon palveluja. Johtopäätös on, että on olemassa hälyttävä ikääntyneiden joukko, joilla on riski olla saamatta terveydenhuollon palveluista sitä hoitoa ja ohjausta, jota he tarvitsevat. On tärkeää löytää ratkaisuja ja tehdä toimia, jotka parantavat ikääntyneiden terveydenlukutaitoa ja vähentävät eroavaisuuksia terveydenlukutaitoisten ja -taidottomien välillä.
Keywords: health literacy, older adults, systematic review, terveydenlukutaito, ikääntyneet, systemaattinen kirjallisuuskatsaus